Identifikasi Variabel yang Berpengaruh terhadap Kinerja Pemasaran dan Indikator Kinerja Pemasaran untuk Industri Hotel - Qurtubi, Qurtubi; Trisnaningtias, Dicka Meilana; Yudhanata, Muhammad Fadhila (Jurnal Sistem dan Manajemen Industri, 2019)
This article discusses marketing performance by identifying marketing mix variables that influence marketing performance and its indicators in the hotel industry. The purpose of this writing was to find the correlation between marketing mix with marketing performance and signs in the hotel industry. This article was expected to extend the insights and provide valuable suggestions for future researches. The method applied in this article was a literature study. The literature study was used systematically towards 24 research articles in the field of marketing performance that written from 2000 to 2018. Based on the results and discussion, it could conclude that marketing mix variables influence marketing performance that covers product, price promotion, and distribution channel. This research also identifies three selected indicators for marketing performance in the hotel industry. Those indicators include customer mindset, expression of customer preference, and customer behavior. The potential future research, among others, is a research that will employ marketing performance indicators that suitable to other service industries.